Experiences of disabled children’s families concerning school-family collaboration - Zoniou-Sideri, Athena; Nteropoulou-Nterou, Eudoxia (International Journal about Parents in Education, 2023)
The role of families in the education of disabled children is one of the prominent factors influencing their educational course. Parents’ aspirations for their children, their expectations and their experiences are determinant factors in the education of their disabled children. In the Greek context the role of familial environment appears reinforced since historically the majority of society has considered education as an individual responsibility of families. The scope of this study is the exploration of the experiences of a group of disabled children’s parents concerning school-family collaboration in relation to the functioning of the special educational structures following discourse analysis approach. The exploration of the experiences of disabled children’s families took place using semi-structured interviews. The analysis of parent’s experiences follows the social model of disability, which is contrasted with the clinical model and the theory of personal tragedy. The discourse analysis approach reveals a growing number of incidents concerning the feeling of personal tragedy. The experience of personal tragedy appears more often at the level of collaboration with structures and professionals from the educational context, projecting the individual model approach of disability at the level of school-family collaboration.